Respuesta :

Answer:

(r+s) (x) = 4x+3

(r*s) (x) =  3x^2 +x-4

(r-s) (-1) =  -3

Step-by-step explanation:

r(x) = x-1

s(x) = 3x+4

(r+s) (x) =  x-1  + 3x+4

Combine like terms

           = 4x+3

(r*s) (x) = ( x-1)  ( 3x+4)

FOIL    

           = 3x^2 +4x-3x-4

           = 3x^2 +x-4

(r-s) (x) =  x-1  - (3x+4)

Distribute the minus sign

           =x-1-3x-4

           =-2x-5

Let x = -1

(r-s) (-1) =  -2(-1) -5

               2-5

                  -3

Answer:

[tex](r + s)(x)=4x+3[/tex]

[tex](r * s)(x)=3x^2+x-4[/tex]

[tex](r - s)(-1)=-3[/tex]

Step-by-step explanation:

We know that:

[tex]r(x) =x-1\\s(x)=3x+4[/tex]

To find [tex](r + s) (x)[/tex] we add the function [tex]r (x)[/tex] with the function [tex]s (x)[/tex]

So

[tex](r + s)(x)=r(x)+s(x)[/tex]

[tex](r + s)(x)=x-1 + 3x+4[/tex]

[tex](r + s)(x)=4x+3[/tex]

To find [tex](r * s) (x)[/tex] we multiply the function [tex]r (x)[/tex] with the function [tex]s (x)[/tex]

So

[tex](r *s)(x)=r(x)*s(x)[/tex]

[tex](r * s)(x)=(x-1)(3x+4)[/tex]

Using the distributive property we have left that

[tex](r * s)(x)=3x^2+4x-3x-4[/tex]

[tex](r * s)(x)=3x^2+x-4[/tex]

To find [tex](r - s) (-1)[/tex] we subtract the function [tex]r (x)[/tex] with the function [tex]s (x)[/tex]  and then evaluate in (-1)

Then:

[tex](r - s)(-1)=r(x)-s(x)[/tex]

[tex](r - s)(-1)=x-1 - (3x+4)[/tex]

[tex](r - s)(-1)=x-1-3x-4[/tex]

[tex](r - s)(-1)=-2x-5[/tex]

[tex](r - s)(-1)=-2(-1)-5[/tex]

[tex](r - s)(-1)=2-5[/tex]

[tex](r - s)(-1)=-3[/tex]